Gestão documental: análise da aplicação dos instrumentos normativos da FUNAI/CTL Belém/PA (2013-2019) - VIEIRA, Bruna Rafaela Reis (2021)
Modern organizations become complex as their information management needs increase, and archiving is an essential unit in the organization of document masses. In this sense, the present study is characterized as an exploratory research, as it aims to understand the process related to the creation and application of normative instruments built through the Documentation Management Policies of the National Indian Foundation (FUNAI), having as its locus the Coordination Belém Local Technique. Thus, to achieve this objective it is necessary to understand the description of the document management process, as well as to analyze the legal structure of the normative instruments. Considering the bibliography studied, and from interviews and questionnaires to the staff of the Intermediate Archive of the Local Technical Coordination of FUNAI in Belém. The analysis of the divergent scenario of the instructions arising from the management guidelines provided by FUNAI.